2022
DOI: 10.1186/s13054-022-03990-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the SAfety and FEasibility of bedside portable low-field brain Magnetic Resonance Imaging in patients on ECMO (SAFE-MRI ECMO study): study protocol and first case series experience

Abstract: Background To assess the safety and feasibility of imaging of the brain with a point-of-care (POC) magnetic resonance imaging (MRI) system in patients on extracorporeal membrane oxygenation (ECMO). Early detection of acute brain injury (ABI) is critical in improving survival for patients with ECMO support. Methods Patients from a single tertiary academic ECMO center who underwent head CT (HCT), followed by POC brain MRI examinations within 24 h fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 10 publications
0
31
0
Order By: Relevance
“…We previously reported that adult patients supported on VA- and VV-ECMO can be safely imaged with a low-field POC brain MRI at the bedside in an ICU setting [ 6 ]. However, a significant proportion of ECMO patients were not enrolled in our study due to the concurrent use of IABP with no available safety data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported that adult patients supported on VA- and VV-ECMO can be safely imaged with a low-field POC brain MRI at the bedside in an ICU setting [ 6 ]. However, a significant proportion of ECMO patients were not enrolled in our study due to the concurrent use of IABP with no available safety data.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, no ABI were detected on POC brain MRI imaging, corresponding to clinical HCT results. In our previous report, we collected four MR sequences: T1-weighted, T2-weighted, fluid-attenuated inversion recovery (FLAIR), and diffusion-weighted imaging with an apparent diffusion coefficient map (DWI ADC), which resulted in an average exam time of 39 minutes [ 6 ]. In this study, the T1 sequence was eliminated, resulting in an average run time of 33 min, without a compromise in diagnostic ability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One study found pMRI to be effective in assessing brain injuries in critically ill patients diagnosed with COVID-19 [9]. Other studies have remarked on the safety, feasibility, and ease of obtaining point-of-care MRIs in various clinical settings using pMRI [10][11][12][13][14]. Furthermore, traditional MRI machines have a magnetic field of 1.5 or 3 T [15][16].…”
Section: Introductionmentioning
confidence: 99%